Human mitochondrial tRNAs: post-transcriptional modifications and diseases - Suzuki, Tsutomu (Henry Stewart Talks, 2018)
Mitochondrial tRNA modification, tRNA modification plays a critical role in protein synthesis, Biogenesis and pathology of taurine modification, Biogenesis and physiology of 5-formylcytidine, Lack of tRNA modification is a primary cause of human mitochondrial disease